The WRF nested within the CESM: Simulations of a midlatitude cyclone over the Southern Great Plains. (17th September 2013) - He, Juanxiong; Zhang, Minghua; Lin, Wuyin; Colle, Brian; Liu, Ping; Vogelmann, Andrew M.
<x xml:space="preserve">Abstract</x> [1] This paper describes an integrated modeling system in which the Weather Research and Forecasting model (WRF) is nested within the Community Earth System Model (CESM). This system is validated for the simulation of a midlatitude cyclongesis event over the Southern Great Plains of the United States. The global atmospheric model CAM4 at T42 resolution in the CESM has missed this cyclogenesis, while the nested WRF at 30 km grid spacing (or finer) that is initialized with the CAM4 condition and laterally forced by the CAM4 successfully simulated the deepening midtropospheric trough and associated cyclogenesis. An analysis of the potential velocity evolution and sensitivity experiments show that it is the higher WRF resolution that allowed the realistic sharpening of the Ertel's Potential Vorticity (EPV) gradient and the ensuing cyclogenesis. The terrain resolution and the physical parameterizations, however, play little role in the difference between the CAM4 and the WRF in the CESM. The integrated WRF/CESM system is intended as one method of global climate modeling with regional simulation capabilities. The present case study also serves as a verification of the system by comparing with standalone WRF simulations forced by operational analyses.